Advances in materials science for environmental and energy technologies II - Materials Science & Technology Conference; Matyáš, Josef; Ohji, Tatsuki; Liu, Xingbo; Paranthaman, M. Parans; Devanathan, Ram; Fox, Kevin; Singh, Mrityunjay; Wong-Ng, Winnie (Ceramic transactions, 2013)
These proceedings contains a collection of 24 papers from five 2012 Materials Science and Technology (MS&T'12) symposia. * Green Technologies for Materials Manufacturing and Processing III * Materials Development for Nuclear Applications and Extreme Environments * Materials Issues in Nuclear Waste Management in the 21 st Century * Energy Conversion – Photovoltaic, Concentrating Solar Power, and Thermoelectric * Energy Storage: Materials, Systems and Applications